How social capital affects innovation in a cultural network: Exploring the role of bonding and bridging social capital. Issue 5 (7th November 2019) - Ceci, Federica; Masciarelli, Francesca; Poledrini, Simone
Abstract : Purpose: The purpose of this paper is to explore how bonding (i.e. tightly knit, emotionally close social relationships) and bridging social capital (i.e. outward looking open social relationships) affect opportunity recognition and innovation implementation in a cultural network of firms, investigating the main benefits of and drawbacks to both bonding and bridging social capital. Design/methodology/approach: The paper is based on a case study of a cultural network of firms which share the same norms, principles and values. The method adopted is content analysis of qualitative data. Findings: The authors find that in cultural network bridging social capital facilitates experimentation and combination of ideas from distant sources, while bonding social capital, which underpins the need for more conformity, is more effective for supporting innovation implementation. Innovation results from the interplay between the two dimensions of social capital, and each dimension contributes to the final outcome in a distinct and unique way. Research limitations/implications: There are some limitations which arise from the case study methodology; the limited set of industries analysed affects the generalizability of the findings. Practical implications: The research has some practical implications for firms that belong to cultural networks. It offers suggestions about how to manage social relationships in different stages of the innovation process. Originality/value: The authors examine the effects of bonding and bridging social capital on innovation in a cultural network of firms. The authors show that in a cultural network, different moments in the innovation process require different efforts related to the firm's network relationships.